Differences In Storage Time In Safranin Dye On Counting The Number Of Platbocytes By Rees Ecker Method - Alya Salsabila; Gilang Nugraha (Poltekkes Kemenkes Mataram, 2024)
Platelet count examination is important to assess hemostasis function. One of the commonly used manual methods is the Rees Ecker method. However, during the examination, impurities were found that were difficult to distinguish from platelets. Therefore, this study aimed to determine the difference in platelet count results using the Rees Ecker method against storage time with safranin dye. This study used an experimental method on 10 normal blood samples. Platelets were counted with an Improved Neubeauer hemocytometer using safranin dye stored for 0 days, 1 day, 7 days, 14 days, and then compared with the platelet count results using Rees Ecker as a control solution. The Mann Whitney Test results showed no significant difference between the control group and the safranin group in terms of platelet count at 0 days (sig. 0.850), 1 day (sig. 0.820), 7 days (sig. 0.130), and 14 days (sig. 0.121) of storage. Safranin is safe and effective for counting platelets using the Rees Ecker method, as shown by the stability test results for 14 days.